2013
DOI: 10.1111/petr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of a classic Hodgkin lymphoma‐type post‐transplant lymphoproliferative disorder with tailored chemotherapy and Epstein–Barr virus‐specific cytotoxic T lymphocytes in a pediatric heart transplant recipient

Abstract: CHL type is the least common major form of EBV-related PTLD but rarely occurs in pediatric recipients; development of CHL subsequent to other PTLD subtypes in the same transplant recipient is even more unusual. Because of its rarity, indications on the best treatment strategy are limited. Patients have been mostly treated with standard HL chemotherapy/radiotherapy, and prognosis seems more favorable than other monomorphic PTLDs. Herein, we describe a pediatric case of EBV-associated, stage IV-B, CHL arising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Additionally, programmed cell death protein 1 (PD‐1) blockade poses as a potential treatment option, due to upregulation of PD‐L1 by EBV. A combination of low‐dose chemotherapy with EBV‐specific cytotoxic T‐cell lymphocytes was also reported to be effective in a case report of HL‐PTLD after heart transplant . Risks of using checkpoint inhibitors include secondary toxicities, such as allograft rejection or acquired autoimmunity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, programmed cell death protein 1 (PD‐1) blockade poses as a potential treatment option, due to upregulation of PD‐L1 by EBV. A combination of low‐dose chemotherapy with EBV‐specific cytotoxic T‐cell lymphocytes was also reported to be effective in a case report of HL‐PTLD after heart transplant . Risks of using checkpoint inhibitors include secondary toxicities, such as allograft rejection or acquired autoimmunity.…”
Section: Discussionmentioning
confidence: 98%
“…A combination of low-dose chemotherapy with EBVspecific cytotoxic T-cell lymphocytes was also reported to be effective in a case report of HL-PTLD after heart transplant. 17 Risks of using checkpoint inhibitors include secondary toxicities, such as allograft rejection or acquired autoimmunity. Further study of the efficacy and toxicity of these new agents may provide more targeted and less toxic therapy for both HL and HL-PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…CHL-type PTLD was previously reported to develop in recipients with other preceding PTLD subtypes, mainly polymorphic-type PTLD ( 6 ); however, difficulties were associated with clarifying the relationship between preceding polymorphic-type and CHL-type PTLDs. In our case, although preceding polymorphic-type PTLD included a small number of large cells as immunoblasts with the expression of PAX5, the immunohistochemical examination did not reveal any expression of CD30 or EBER, indicating a less-common manifestation of these cells between polymorphic-type and CHL-type PTLDs.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the treatment of HL‐PTLD is even more scant and has been primarily restricted to case reports and case series totaling 39 patients . Chemotherapy has been commonly administered, although follow‐up varied greatly across reports.…”
Section: Discussionmentioning
confidence: 99%
“…Disease outcomes and prognostication for patients who develop HL‐PTLD are not well described. Most available data on the treatment of HL‐PTLD have been reported in case reports and small series , and thus, there is minimal guidance when evaluating and treating this unique patient population. One registry study identified 60 patients with HL‐PTLD in renal transplant recipients, all of whom were diagnosed prior to 2001 .…”
Section: Introductionmentioning
confidence: 99%